Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) Melalui Program Strategis Dinas Koperasi dan UMKM Kabupaten Lombok Timur - Salmi Yuniar Bahri; Abdul Halik; Siti Mujanah (Pusat Riset dan Inovasi Nasional, 2026)
This study focuses on the development of Micro, Small, and Medium Enterprises (MSMEs) through the strategic programs implemented by the Office of Cooperatives and MSMEs of East Lombok Regency. MSMEs play a vital role in improving community welfare and driving regional economic growth. The local government seeks to strengthen this sector through various empowerment policies and initiatives. The purpose of this study is to examine and describe the efforts to develop MSMEs through the strategic programs of the Office of Cooperatives and MSMEs, as well as to identify the supporting and inhibiting factors influencing their implementation. The research employs a qualitative descriptive method, with data collected through observation, interviews, and documentation, and analyzed using the stages of data reduction, presentation, and conclusion drawing. The findings indicate that the strategic programs include enhancing human resource capacity, facilitating access to financing, expanding market access, and providing business mentoring. These programs have contributed positively to improving the productivity and independence of MSME actors. Supporting factors include government support, partnerships with financial institutions, and strong entrepreneurial enthusiasm, while inhibiting factors involve low digital literacy, limited managerial capacity, and challenges in the distribution of financial aid. Overall, the strategic programs of the Office of Cooperatives and MSMEs play a crucial role in strengthening the competitiveness and sustainability of MSMEs in East Lombok Regency.